Introducing the Escalation Antibiogram: A Simple Tool to Inform Changes in Empiric Antimicrobials in the Nonresponding Patient. (5th April 2022) - Teitelbaum, Daniel; Elligsen, Marion; Katz, Kevin; Lam, Philip W; Lo, Jennifer; MacFadden, Derek; Vermeiren, Christie; Daneman, Nick
Abstract: Background: Hospital antibiograms guide initial empiric antibiotic treatment selections, but do not directly inform escalation of treatment among nonresponding patients. Methods: Using gram-negative bacteremia as an exemplar condition, we sought to introduce the concept of an escalation antibiogram. Among episodes of gram-negative bacteremia between 2017 and 2020 from 6 hospitals in the Greater Toronto Area, we generated escalation antibiograms for each of 12 commonly used agents. Among organisms resistant to that antibiotic, we calculated the likelihood of susceptibility to each of the other 11 agents. In subgroup analyses, we examined escalation antibiograms across study years, individual hospitals, community versus hospital onset, and pathogen type. Results: Among 6577 gram-negative bacteremia episodes, the likelihood of coverage was ampicillin 31.8%, cefazolin 62.7%, ceftriaxone 67.1%, piperacillin-tazobactam 72.5%, ceftazidime 74.1%, trimethoprim-sulfamethoxazole 74.4%, ciprofloxacin 77.1%, tobramycin 88.3%, gentamicin 88.8%, ertapenem 91.0%, amikacin 97.5%, and meropenem 98.2%. The escalation antibiograms revealed marked shifts in likelihood of coverage by the remaining 11 agents. For example, among ceftriaxone-resistant isolates, piperacillin-tazobactam susceptibility (21.2%) was significantly lower than trimethoprim-sulfamethoxazole (54.2%, P < .0001), ciprofloxacin (63.0%, P < .0001), ertapenem (73.4%, P < .0001), tobramycin (80.1%, P < .0001), gentamicin (82.8%, P < .0001), meropenem (94.3%, P < .0001), and amikacin (97.1%, P < .0001). Trimethoprim-sulfamethoxazole was the second-ranked agent in the meropenem escalation antibiogram (49.6%) and first in the amikacin escalation antibiogram (86.0%). Escalation antibiograms were consistent across 4 study years and 6 hospitals. Conclusions: Escalation antibiograms can be generated to inform empiric treatment changes in nonresponding patients. These tools can yield important insights such as avoiding the common maneuver of escalating from ceftriaxone to piperacillin-tazobactam in suspected gram-negative bacteremia. Abstract : Using gram-negative bacteremia/sepsis as an example, we introduce the concept of escalation antibiograms. Escalation antibiograms express likelihood of coverage by other antibiotics, conditional on resistance to another agent, and can thereby inform modifications of empiric treatment in nonresponding patients.